Effect of dietary sodium selenite, Se-enriched yeast and Se-enriched Chlorella on egg Se concentration, physical parameters of eggs and laying hen production - Skřivan, M.; Šimáně, J.; Dlouhá, G.; Doucha, J. (Czech Journal of Animal Science, 2006)
ISA Brown laying hens at 24 weeks of age, housed in laying battery cages, were used in this 4-group experiment. One group was fed a basal diet containing primarily maize, soybean meal and wheat. Selenium (Se) content of the basal diet was 0.07 mg/kg dry matter. The other hens received diets supplemented with Na2SeO3, Se-enriched yeast and Se-enriched alga Chlorella, respectively, in a concentration of 0.3 mg Se/kg. The experiment lasted twenty-seven weeks. Egg production, feed consumption, egg weight, physical parameters of egg white, yolk and egg shell were examined every third week and egg white and yolk Se content repeatedly. Se was determined by inductively coupled plasma mass spectrometry. All three sources of added Se increased the egg white and egg yolk Se content (P < 0.001). Selenium in the organic form increased further Se in the egg components compared to sodium selenite (P < 0.001). More Se was deposited in egg white than in egg yolk, especially in relation to the increasing time of the experiment. The increase of Se concentration in egg white corresponded with increasing egg white weight in both organic selenium sources (P < 0.05). Higher egg white thickness and better Haugh units were observed only in the Se-Chlorella group. Hens receiving the diet with Se-Chlorella also had better egg production compared to the basal diet (P < 0.05). Egg weight was significantly higher in the Se-Chlorella and Se-yeast groups compared to the basal diet and the diet with sodium selenite (P < 0.05). The Se-enriched alga Chlorella showed summarily best results.
Keywords: sodium selenite; Se-yeast; Se-Chlorella; laying hens; Se in eggs; Haugh unit; hen production